Meiose e genética mendeliana: proposta de uma sequência didática participativa e investigativa - Jeovanio José da Rocha (2019)
Knowledge in genetics is essential so students can understand other fields of modern biology, and also to become critical citizens able to understand the advances that interfere with life in society, such as medical and agricultural issues, for example. Meiosis is considered a difficult subject to understand by high school students which may hinder construction of knowledge related to basic genetics. In addition, this topic is fundamental for students to understand various topics such as gametogenesis, reproduction, evolution and among others. Thus, this study aimed at contributing to the teaching and learning of genetics, through the development, application and evaluation of an investigative didactic sequence that addressed meiosis related to Mendelian genetics. The target audience of this study was students from the 3rd year of a state school in Brumadinho, MG. The proposed sequence is developed in nine classes and low cost and easily accessible materials are used. Various activities were planned around a previously published practice entitled Meiosis on Paper, which has the handling of paper-cut chromosomes as the main link for learning meiosis and Mendelian genetics. The introduction to the theme was guided by the formation of gametes and fertilization. It was not noticed that students had a great commitment and willingness to participate in the classes. The analysis of the initial and final questionnaires indicated that more students gave correct answers on the subjects related to meiosis and the principles of Mendelian genetics. With this work it was possible to create an innovative didactic sequence that allowed students to have a better interaction, participation and group work, allowing them to be protagonists in the construction of their knowledge. The product of this work was, thus, the creation of a manual for the teacher about the didactic sequence which also includes detailed guidelines for the student. Keywords: genetics teaching; meiosis; didactic sequence.